Scenarios for Coal-Exit in Germany—A Model-Based Analysis and Implications in the European Context - Martin Kittel; Leonard Goeke; Claudia Kemfert; Pao-Yu Oei; Christian R. von Hirschhausen (Energies, 2020)
The political discussion to reduce the carbon footprint of Germany's electricity sector, focusing on coal, is intensifying. In this paper, we develop scenarios for phasing out lignite and hard coal power plants in Germany prior to the end of their technical lifespan (“coal-exit”). Our analysis bases upon two coal-exit instruments, the retirement of coal generation capacities and the limiting of how much aged coal power plants with high carbon intensity can be used within a year. Results show that phasing out coal in Germany would have a considerable impact on Central European electricity markets, in terms of decarbonization efforts and electricity trade. An ambitious coal-exit could avert foreseeable shortcomings in Germany's climate performance in the short-run and release additional carbon savings, thus compensating for potential shortfalls in other energy-intensive sectors by 2030. Limited emissions in the range of 27% would be shifted to neighboring countries. However, tremendous positive climate effects on European scale would result, because Germany's annual emission savings in 2030 would be substantial. Totaling 85 million tons of CO2, the overall net reduction is equivalent to 17.5% of total European emissions in 2030 without retirements of coal-firing power plants prior to the end of their technical lifespan.
Keywords: 330; Energy transition; Germany; Energiewende; Electricity modeling; Coal phase-out; Energy policy; Climate policy